Claws for alarm - Conte, Cate (A Cat Cafe Mystery, 2021)
Maddie James has finally given in to her friend Katrina’s pleas to open up her cat cafe to more than ten felines: they’re now up to fifteen purring friends. In fact, JJ’s House of Purrs is making such a splash that she’s getting national attention. The East Coast Animal Rescue League is quite interested in the cafe, and so Maddie accepts a request to meet with Jillian Allen, the executive director. Jillian shows up at the cafe and asks Maddie if they can partner on a fundraiser to support the local rescue efforts—and she offers up her celebrity endorser and her celebrity cat to sweeten the deal. Maddie, caught up in the prospect, offers up her sister Val to help plan the event. But when Val shows up for a site visit at the venue, she finds Jillian strangled with a fancy cat leash—a piece of swag they were intending to use for the fundraiser—leaving Maddie with a lot of questions to answer. Was her death a tragic one-off event, or is there something more sinister going on? Maddie has to figure it out fast, before anyone else in the rescue community is jeopardized.